1971
DOI: 10.1007/bf00184783
|View full text |Cite
|
Sign up to set email alerts
|

Leaf temperature measurement techniques

Abstract: Three types of thermocouple sensing elements were used to measure potato leaf temperatures in the uppermost layer of the canopy. A comparison between thermocouple hypodermic needles inserted into the midrib of the potato leaf and thermocouple clips fastened on its surface gave near-identical temperature readings. Miniature screens housing thermocouple sensors exposed at the upper canopy level and measuring ambient air temperatures showed excellent agreement (r = 0.996, N= 68) with potato leaf temperatures. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…Two ways are possible: direct or indirect measurement. Direct measurement consists of putting small sensors on each organ for radiation (Gutschick et al ., 1985) or temperature (Lomas et al ., 1971) (Fig. 5) or near each organ for air features (Grantz & Vaughn, 1999; Wang et al ., 1999).…”
Section: What Is Phylloclimate?mentioning
confidence: 99%
“…Two ways are possible: direct or indirect measurement. Direct measurement consists of putting small sensors on each organ for radiation (Gutschick et al ., 1985) or temperature (Lomas et al ., 1971) (Fig. 5) or near each organ for air features (Grantz & Vaughn, 1999; Wang et al ., 1999).…”
Section: What Is Phylloclimate?mentioning
confidence: 99%
“…The air must therefore have been heated by foliage considerably warmer than itself. However, this conclusion has been disputed by Lomas et al [1971], and the difficulty in obtaining representative measurements is probably responsible for the uncertainty. If the model is rerun with the stomatal resistance increased by a factor of !00, but with all else the same, the maximum foliage temperature reaches a value 5.5 K warmer (12.0 K warmer for at = 1), which is an example of 'foliage fever.'…”
Section: Diagnose Tr From the Foliage Energy Budget Equation (32) By mentioning
confidence: 99%
“…Frequency of radiation reflected by plant leaves (8970–9890 nm) is shifted towards longer wavelengths in respect to solar radiation (300–2000 nm) reaching their surface (Peñuelas and Filella 1998 ; IRT_protocol 2015 ). Thus, sun-exposed leaves’ temperature could rapidly rise by as much as 10 °C relative to shaded leaves (Ansari and Loomis 1959 ; Lomas et al 1971 ; SEOS 2015 ). Our data similarly indicated that the sun-exposed mines’ temperature exceeded air temperature by 10 °C (even 20 °C in a single measurement) within minutes.…”
Section: Discussionmentioning
confidence: 99%